Timid fiends by Fyodor Dostoyevski. A metaphysical experiment - Polaczek, Monika (Folia Philosophica, 2008)
The article is a philosophical interpretation of the problem of an experimental murder and suicide in works by Fyodor Dostoyevski. The literary language of the Russian writer is treated here as a medium of his philosophical voice. The text is an analysis of the so called „metaphysical experiment” the literary exemplification of which is murder and suicide committed by the characters of Crime and Punishment. The exact procedure of the experiment attempting at defining its own place in the structure of beings by a free subject, as well as the consequences of the experiment treated like that were described. The analysis of a metaphysical experiment and its teleological efficiency was to show the basic mistake made by an individual conducting an experiment. The mistake itself is an unverified statement that the area of a material reality can be the proper place of constituting the theses concerning the transcendent sphere.